“Jetzt bist du in Deutschland, Däumling.”: Nils Holgersson on Foreign Soil – Subject to New Norms - Desmidt, Isabelle (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2003)
AbstractThe German words in the title are taken from the first German translation of the Swedish children’s book Nils Holgerssons underbara resa genom Sverige (Nils Holgersson’s wonderful journey throughout Sweden, Lagerlöf 1906-1907). In this translation Nils is said to land in Germany, which is never the case in the Swedish original. Presumably, the German translator Klaiber added this extra visit to oblige the German readers with a visit of Nils to their own country. Looking at some of the German versions of Nils Holgersson, this article addresses the influence of extratextual factors, i.e., different kind of norms, on the translating and rewriting process.